PENERAPAN PEMBELAJARAN KONTEKSTUAL DENGAN PENGUATAN PROFIL PELAJAR PANCASILA DIMENSI GOTONG ROYONG DI KELAS IV SDN BANYUMANIK 03 - Sholikhatun, Umi; Ulia, Nuhyal; Jupriyanto, Jupriyanto (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The background of this research is the importance of creating learning that is able to accommodate the knowledge that students already have from the surrounding environment and apply character values in every lesson, as a manifestation of the Pancasila Learner Profile. Therefore, this research aims to analyze the application of contextual learning methods, identify the strengthening of the gotong royong dimension in the Pancasila Learner Profile through Project Based Learning, and find out how it impacts on students' involvement and enthusiasm. The method used is qualitative with a descriptive approach, including observation, interviews, and documentation. The results of this study show that project-based contextual learning is able to increase students' active participation and enthusiasm for learning. In addition, this method is effective in instilling mutual cooperation values, such as cooperation, social care, and sharing attitude. Evaluation of students' learning outcomes also showed a good understanding of energy change material. This research provides implications for teachers and prospective teachers to design learning that is more meaningful and engaging.